2004
DOI: 10.1007/s00125-004-1556-7
|View full text |Cite
|
Sign up to set email alerts
|

?2-Heremans?Schmid glycoprotein gene polymorphisms are associated with adipocyte insulin action

Abstract: Our results are in agreement with a threshold model of susceptibility for insulin resistance and type 2 diabetes, in which specific genetic loci regulate intermediate molecular phenotypes. When an individual's set of susceptibility alleles at such loci exceeds a threshold, clinical disease occurs. Lipolysis in adipocytes appears to be a phenotype that is particularly sensitive to variation in AHSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
4
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 22 publications
4
53
4
2
Order By: Relevance
“…The biological function of AHSG and the Ahsg knockout mouse, as well as the chromosomal localization of AHSG, suggest a potential involvement of AHSG variation in the pathogenesis of metabolic diseases (2,7,10,11), and previous genetic epidemiological studies have shown association of AHSG variants with obesity (14), type 2 diabetes (15), and plasma cholesterol levels (12). In the present study we aimed at replicating these findings by genotyping the previously investigated variants, as well as AHSG tagSNPs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The biological function of AHSG and the Ahsg knockout mouse, as well as the chromosomal localization of AHSG, suggest a potential involvement of AHSG variation in the pathogenesis of metabolic diseases (2,7,10,11), and previous genetic epidemiological studies have shown association of AHSG variants with obesity (14), type 2 diabetes (15), and plasma cholesterol levels (12). In the present study we aimed at replicating these findings by genotyping the previously investigated variants, as well as AHSG tagSNPs.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, attempts have been made to associate AHSG variation with metabolic phenotypes. Three polymorphisms (Ϫ843AϾT/rs2248690, Ϫ469TϾG/rs2077119, and Thr248Met/rs4917) were associated with plasma cholesterol among 291 Swedish women for whom a relationship of Ϫ469TϾG with insulin-mediated inhibition of lipolysis was also shown (12). Thr248Met and Thr256Ser (rs4918), which are in almost perfect linkage disequilibrium (LD), were examined among 176 Japanese subjects in relation to serum concentrations of AHSG, which proved to be largely dependent on AHSG Thr248Met and Thr256Ser genotypes (13).…”
Section: Research Design and Methods-mentioning
confidence: 99%
“…24 Abdominal subcutaneous fat biopsies were obtained and basal and hormone (chatecholamines and insulin)-stimulated lipolysis and lipogenesis investigated as described previously. 25 mRNA quantification Total RNA was prepared using the RNeasy Mini Kit (Qiagen GmbH, Hilden, Germany). RNA samples were treated with RNase-free DNase (Qiagen GmbH).…”
Section: Phenotypic Evaluationmentioning
confidence: 99%
“…Cohort 2 was genotyped using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (Sequenom Inc., San Diego, CA, USA) as described. 25 Primers are provided on request. Evaluation of genotyping accuracy is described in the 'Results' section.…”
Section: Phenotypic Evaluationmentioning
confidence: 99%
“…140 SNPs in the human AHSG gene have been reported to be associated with adipocyte insulin action, obesity and T2DM. [141][142][143] Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) is an inhibitor of insulin-receptor tyrosine kinase. One ENPP1 haplotype is associated with childhood and morbid obesity, T2DM, as well as circulating levels of ENPP1.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%